(untitled) (Academicia Globe: Inderscience Research, 2024)
This article discusses the possibilities of modular educational technology in teaching literature, the adaptation of its educational process to the individual needs of students, the development of creativity and critical thinking, the features of modular educational technology and its application in teaching literature, methods of active involvement of students, group discussions, creative tasks and interdisciplinary projects, fully explains the role of technologies in the Learning.